KINERJA TINGGI MENINGKATKAN PRILAKU EKONOMI DOSEN - MULIAWAN, AGUS (Jurnal Ilmiah Educational Management, 2015)
This study aims to examine and analyze the effect of performance on behavioral economic lecturer. This study uses a quantitative approach to economics university faculty survey method palangkaraya. Data taken from 45 lecturers. Data analysis technigues using path analysis. The results showed that the performance of the direct positive effect on the economic behavior of lecturers.